2009
DOI: 10.1897/08-145.1
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of multiple stressors on growth and metabolic rate of Malaclemys terrapin

Abstract: Coastal species encounter numerous physiological stressors ranging from daily fluctuations in salinity and temperature to anthropogenic contaminants, yet the effects of such stressor combinations on aquatic organisms remain largely unknown. Exposure to environmental contaminants, such as polychlorinated biphenyls (PCBs), can disrupt physiological processes, and while physiological responses to salinity change are well understood, the combined effects of salinity change and contaminants on these processes are u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 36 publications
2
19
1
Order By: Relevance
“…In other turtle species, a variety of clinical health parameters were affected by PCBs (Keller et al, 2004), which could translate to whole organism responses leading to decreased growth. More corroborative of our approach to modeling PCB effects on growth are two recent studies on diamondback terrapins in which significant effects of a single intraperitoneal injection of 20 mg/g PCB-126 on growth of juvenile turtles were observed (Holliday et al, 2009;Holliday and Holliday, 2012). Following the 180 day post-exposure period, turtles exposed to PCB-126 were approximately 11% smaller than control turtles.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…In other turtle species, a variety of clinical health parameters were affected by PCBs (Keller et al, 2004), which could translate to whole organism responses leading to decreased growth. More corroborative of our approach to modeling PCB effects on growth are two recent studies on diamondback terrapins in which significant effects of a single intraperitoneal injection of 20 mg/g PCB-126 on growth of juvenile turtles were observed (Holliday et al, 2009;Holliday and Holliday, 2012). Following the 180 day post-exposure period, turtles exposed to PCB-126 were approximately 11% smaller than control turtles.…”
Section: Discussionsupporting
confidence: 54%
“…We also separately evaluated projected impacts of PCBs on growth beyond year 2 juveniles by assuming a 5, 10 or 15% reduction in yearly growth rate in PCB-exposed snapping turtles. This evaluation of a PCBinduced effect on growth rate is justified based on observed impacts of PCBs on snapping turtles (Eisenreich et al, 2009) as well as effects of PCBs on growth rates in diamondback terrapins (Holliday et al, 2009;Holliday and Holliday, 2012). Specifically, Holliday et al, 2009 observed significant effects on growth and metabolism following intraperitoneal injection of PCBs to diamondback terrapins.…”
Section: Model Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dose-response studies provide an avenue of inquiry and indicate that PCBs can cause adverse impacts to individual turtles (e.g. Eisenreich et al 2009, Holliday et al 2009, Holliday & Holliday 2012, Yu et al 2012. Such studies can be advantageous for isolating the effect of exposure level to a particular contaminant on the performance of specific traits of individuals; however, implications of such studies of population-level endpoints remain unclear.…”
Section: Introductionmentioning
confidence: 99%